Urban Poverty in the Global South : Scale and Nature. - Mitlin, Diana (Taylor and Francis, 2012)
One in seven of the world's population live in poverty in urban areas, and the vast majority of these live in the Global South - mostly in overcrowded informal settlements with inadequate water, sanitation, health care and schools provision. This book explains how and why the scale and depth of urban poverty is so frequently under-estimated by governments and international agencies worldwide. The authors also consider whether economic growth does in fact reduce poverty, exploring the paradox of successful economies that show little evidence of decreasing poverty. Many official figures.